Studi Literatur Sejarah Dan Perkembangan Kejadian Anisakiasis Di Indonesia - De Jesus, Christina Debby; Detha, Annytha I.R; Almet, Julianty (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
Anisakiasis is a zoonotic foodborne disease that infects humans caused by infection with stage III larvae of the nematode worms Anisakis spp., Where the transmission of stage III larvae Anisakis spp. to humans occurs when humans eat raw marine fish. This literature study aims to see the history of the development of anisakiasi in Indonesian waters. In world history, anisakiasis began to occur in the 1960s since an endemic case in the Netherlands (1962) was reported by Van Thiel due to the high consumption of salt fish. Meanwhile, in Indonesia the incidence of anisakiasis in fish was the first time in Sulawesi in 1954 and in 1996 the first incidence of anisakiasis in humans was in Sidoarjo, East Java. Based on the development of Anisakiasis in fish and humans, it can be predicted that it will affect the distribution of anisakis widely and pose risks to aspects of community life, including socioeconomic, environmental, public health and tourism. Until now, investigating shows that the prevalence of anisakis in several regions of Indonesia such as Sumatra, Sulawesi, Java, Bali and NTT is high, where the results of molecular indications indicate that A. tipica has a higher prevalence compared to anisakis species in Indonesian waters.